Dental Caries Experience of Down's Syndrome Children in Ajdabiya - Libya - Mansur, Eman (Libyan Journal of Dentistry, 2019)
Aims: Assessment of the caries experience of Down’s Syndrome children who are attending special needs institute in Ajdabiya City, Libya. Methods: A descriptive cross-sectional study was used. The total eligible sample comprised 35 DS children, 17 of them males and 18 females, aged between 6 and 15 years. Participants were examined for dental caries, using the decayed, missing and filled teeth index (DMFT/ dmft) according to the WHO criteria. Results: The caries prevalence among the study group was 97.1%. The mean DMFT /dmft scores were 5.705 ± 4.468 and 4.388 ± 3.327 in males and females respectively. There was no difference between means of males and females. In the 6-10 years age group, the mean dmft score was 5.8 ± 4.798, and in the 11-15 years age group, the mean DMFT score was 4.45 ± 3.119. There was no difference between means of both age groups. There was no significant difference between male and female in the 11-15 years age group. There was significant difference between male and female in the 6-10 years age group. Conclusion: The caries prevalence and severity was high among the studied Down’s Syndrome children.